Cities on the agenda: Urban governance and sustainable development - Finn Stepputat; Roanne van Voorst (Danish Institute for International Studies (DIIS), 2016)
Urbanization is a defining trait of the 21st century, and cities are decisive for the future of sustainable development. This has been recognized internationally through the definition of a stand-alone goal for sustainable urban development, the SDG 11. Cities represent extremely serious problems, but they also offer huge potentials for changing the course of action on climate change and other challenges. A new DIIS report takes stock of the field of sustainable urban development and the implications for how Denmarks international engagement could strengthen its focus on cities as part of the SDG agenda. It looks at the state of the art in research on urban governance and sustainable development; it maps current trends and actors in the global political arena for sustainable urban development; and it includes a case study of Jakarta to show how the politics of sustainable development play out in a dynamic but flood-prone megacity. The report recommends that the Danish Government takes the SDG 11 as an occasion to focus on cities as part of Danish support for the implementation of the Sustainable Development Goals. A focus on cities allows a range of Danish actors to engage in international cooperation, including municipalities, public utilities and the private sector. Urban governance is a key challenge and the pervasive informality and fragmented authority of many cities have to be taken into account. In particular intermediate and smaller cities with high population growth need strategic international engagement, and special attention should be given to cities that have become safe havens for displaced populations in areas of conflict.
Keywords: 300